Gestodene, a novel positive allosteric modulator of PAR1, enhances PAR1-mediated human platelet aggregation - So-Hyeon Park; Yunkyung Heo; Il Kwon; Sungwoo Jo; Hyejin Jeon; Yechan Lee; Jieun Kim; Ji Hoe Heo; Wan Namkung; Wan Namkung (Frontiers Media S.A., 2024)
Background: Protease-activated receptor 1 (PAR1) is expressed in human platelets and can be activated by low concentrations of thrombin. Vorapaxar, a selective antagonist of PAR1, inhibits thrombin-induced calcium mobilization in human platelet, which is associated with an increased risk of bleeding. Conversely, the administration of a positive allosteric modulator (PAM) of PAR1 may pose a substantial risk of thrombosis due to inducing excessive platelet activation. In this study, we discovered a novel PAM of PAR1 and investigated the effect of enhanced PAR1 activation by PAM of PAR1 on platelet activation.Methods: To find PAMs of PAR1, a cell-based screen was performed in HT29 cells, and finally, gestodene, an oral contraceptive drug (OC), was identified as a novel PAM of PAR1. The mechanism of action of gestodene and its effects on platelet activation were investigated in human megakaryocytic leukemia cell line MEG-01 cells and human platelet.Results: Gestodene enhanced both thrombin- and PAR1-activating peptide (AP)-induced intracellular calcium levels in a dose-dependent manner without altering PAR2 and PAR4 activity. Gestodene significantly increased PAR1-AP-induced internalization of PAR1 and phosphorylation of ERK1/2, and the enhancing effects were significantly blocked by vorapaxar. Furthermore, gestodene potently increased PAR1-AP induced morphological changes in MEG-01 cells. Remarkably, in human blood, gestodene exerted a robust augmentation of PAR1-AP-induced platelet aggregation, and vorapaxar effectively attenuated the gestodene-induced enhancement of platelet aggregation mediated by PAR1.Conclusion: Gestodene is a selective PAM of PAR1 and suggest one possible mechanism for the increased risk of venous thromboembolism associated with OCs containing gestodene.